Charcoal rot due to Macrophomina phaseolina and its relation with pith disintegration and nodal colonization in Sorghum bicolor - PRABHAKAR and M.Y. SAMDUR, ASHOK V. GADEWAR*, Y.D. NARAYANA, (Indian Phytopathology, 2013)
Investigations carried over multiple years (2008-12) on 305 genetically different sorghum test lines revealed that incidence of charcoal rot, length of pith disintegration, and nodes colonized by Macrophomina phaseolina is significantly related. The strength of relationships between charcoal rot to length of pith disintegration was significantly fair (r=0.404) whereas relation of charcoal rot incidence to nodes colonized was good (r= 0.522). However, the relationship varied from trial to trial which ranged from fair to high both in case of charcoal rot to length of pith disintegration(r=0.430 to 0.899) and nodal colonization (r=0.417 to 0.926). Similar correlation analysis on resistant, tolerant, and susceptible cultivars (varieties/hybrid) showed that the relations fluctuated between negative to positive with different strength and/or were significant or insignificant that varied with cultivars thereby indicating that pith disintegration and nodal colonization is not always influenced by charcoal rot disease incidence. Therefore the study reveals that charcoal rot disease incidence may not predict the extent pith rot or colonization by M. phaseolina with high confidence.